ANALYSIS OF INFORMATION REQUEST AND PUBLIC COMPLAINT SERVICES AT THE PPID OF CENTRAL JAVA PROVINCE TRANSPORTATION DEPARTMENT FROM RESPONSIVE GOVERNANCE PERSPECTIVE - Khairunnisa Intan Nursita; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
Transparency of public information and government responsiveness are important principles in realizing responsive governance. This study focuses on the public information request and complaint services organized by the Information and Documentation Management Officer (PPID) at the Central Java Provincial Transportation Department. Through these services, the government can identify public needs, questions, and complaints, so the ability to respond to services is an important aspect in assessing responsive government practices. However, in practice, there is still a gap between the initial response to complaints and the follow-up to their resolution. This study aims to analyze the responsiveness of public information request and complaint services at the PPID of the Central Java Provincial Transportation Department and identify factors that influence it from a responsive governance perspective. The research approach used is descriptive qualitative, with data collected through in-depth interviews, direct observation, and documentation studies. The results of the study are expected to provide an overview of the level of responsiveness of public information and complaint services at the PPID of the Central Java Provincial Transportation Department and serve as recommendations for improving the quality of public information services and follow-up to handling public complaints.